The concept of beneficial ownership and its application in sukuk issuances : an assessment from the islamic legal perspective - Klopic, Nermin (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
Equity was introduced in the middle ages with the aim to elevate hardship and injustice caused by strict and rigid interpretations of the English law. One of the most significant results of the equity was the concept of trust. The trust is based on segregation of ownership rights over one asset between two or more persons. Effectively, in a trust one asset may have two independent owners, namely, legal and beneficial owner. Considering that in contemporary times the concept of trust is employed in a number of shariah complaint financial products generally and in sukuk issuances specifically, the study aims to find out whether the beneficial ownership is compatible with the requirements of al-milkiyyah in the Islamic law. Based on the Islamic law's principles, only person who holds ownership (al-milkiyyah) over one asset is entitled to revenue from such asset. If an asset is subject to ownership of legal and beneficial owner, which one of them is entitled to the revenue. Given the nature of this study a qualitative methodology is adopted. Relevant references have been examined with the aim to establish, (i) true nature of al-milkiyyah; (ii) true nature of beneficial ownership; and (iii) application of beneficial ownership in Sukuk issuances. Outcomes of the three investigations are used as platform to conceptualize beneficial ownership from the perspecrive of the Islamic legal system. The study reveals that segregation of the ownership rights between two or more persons is an acceptable doctrine in the shariah. It also shows that the ownership of a beneficiary bears significant similarity to the ownership of a minor in guardianship arrangement and the ownership of a beneficiary in an endowment from the perspective of ownership rights. Premised on these and other findings our conclusion is that the concept of beneficial ownership is compatible with the requirements of al-milkiyyah. This compatibility is subject to that jurisdication in which this concept is used in Shari'ah compliant transaction treats ownership rights of the beneficariy as right in rem, not as right in personam. Provided this condition is observed, use of beneficial ownership in sukuk issuances is therefore Shari'ah compliant.